Kako približati šolsko knjižnico otrokom z disleksijo - Bizjak, Breda (Revija za elementarno izobraževanje, 2012)
How to familiarise dyslexic children with school library. The article introduces dyslexia and the causes for its occurrence and outlines the problems that dyslexic people normally face. Reading is one of the biggest issues that affect people with dyslexia. In improving the quality of reading literacy, libraries school libraries in particular can play an important part. Moreover, this article introduces international guidelines regarding library services for people with dyslexia. The role of a librarian as a mediator between a dyslexic child and a book is also presented. The more encouraging and helpful a librarian is, the more successful children with dyslexia can be. Furthermore, the article focuses on the room of a school library and the aids in it, which can make it easier for dyslexic children to get around. Also, it is very important that the reading material and the books are designed in such a way that gives children with dyslexia more time for comprehension. Choosing the books that are appropriate for dyslexic children contributes a lot to their positive self-esteem.